Assessment of Radiation Dose Level in the Farm Soil of Federal University Wukari, Northeast Nigeria - Kilian, Ayuni Ngo; Saleh, Samuel; Sani, Yusuf; Unim, Unim Emmanuel (Darul Yasin Al Sys, 2024)
The study has assessed the amount of radiation exposed to farm soils of federal university Wukari, Taraba State with the aim to determine radiation dose in soils and to provide necessary information of human health risks associated with high radioactivity in soil and its effects on plant materials. Ten different soil samples were collected from different location in the farming soil and the Geiger Muller counter was used to measure the level of radiation exposure in the samples. The analyzed results showed low amount of radiation dose level. The absorbed dose values ranging between 0.1607 Gy/hr - 0.1730Gy/hr while equivalent dose rate ranges between 0.2815mSv/yr - 0.2956mSv/yr. These results revealed that the dose rate does not exceed the recommended values by International Commission on Radiological Protection (ICRP) which is 1 mSv/yr for the general public and therefore do not pose a significant health hazard. The radiation dose level has no negative effect on both the plants and the dwellers. Therefore, the study area is safe for human activities.